Queering Disney animated films using a critical literacy lens. Issue 2 (3rd April 2019) - Fan, Jason
Abstract: Actively queering popular culture texts, using critical literacy tools, is a useful classroom practice that enables agentic readers to see the possibilities for extending their own "queering" of popular culture. Queer readings of Disney animated films, for example, can help challenge the gender norms represented in these films. Through queer re-interpretations of The Lion King and Frozen, I demonstrate how it is possible to create queer meanings that interrupt heteronormativity and imagine worlds that are inclusive of diverse sexualities.